On the microscopic structure of liquid hydrogens - Zoppi, M.; Celli, M.; Bafile, U.; Guarini, E.; Neumann, M. (Condensed Matter Physics, 2001)
Among the quantum liquids, the hydrogens cover an interesting position between liquid helium, where quantum exchange gives rise to the macroscopic phenomenon of superfluidity, and neon, where quantum effects are relatively small, so that its features can be evaluated by perturbation methods with reference to a classical system. Nonetheless, the experimental access to the microscopic structure of the hydrogens is not an easy task both because of their intra-molecular structure and the small molecular mass that is comparable with that of the neutron probe. In this paper we discuss the state of the art and summarise the available experimental information on the microscopic structure of the hydrogens. The experimental data for the two systems are compared among them and with the results of quantum Path Integral Monte Carlo simulations. It is found that similar quantities, measured in corresponding thermodynamic points, are rather different for the two systems due to the different weight of quantum effects. Moreover, the comparison with the simulation results shows that, for deuterium, there is a substantial agreement, both at the level of the structure factor and its thermodynamic derivatives. The agreement is less satisfactory for liquid hydrogen.